2018
DOI: 10.1002/gps.4879
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions and unmet needs for assistance to perform activities of daily living among older adults with dementia in Chile

Abstract: The results from this study call for action by practitioners and policymakers to foster caregiver training, increase supportive services, and advance care planning for PWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Regardless of this variety, a higher dependency on and need for services is common among people with different types of memory disorders [10][11][12]. Previous research shows that higher needs entail unmet needs; hence, people with dementia have more unmet needs than people without dementia [22]. In a study of community-dwelling older people with cognitive impairment and their informal caregivers in the United States, almost all of the older people had at least one unmet need [23].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of this variety, a higher dependency on and need for services is common among people with different types of memory disorders [10][11][12]. Previous research shows that higher needs entail unmet needs; hence, people with dementia have more unmet needs than people without dementia [22]. In a study of community-dwelling older people with cognitive impairment and their informal caregivers in the United States, almost all of the older people had at least one unmet need [23].…”
Section: Discussionmentioning
confidence: 99%
“…Unmet needs are not distributed equally. Some subgroups such as those without a partner and with low socioeconomic position experience more unmet needs [6][7][8][9]. Some studies have also found sex differences in unmet needs among people with dementia; in a Chilean study unmet needs were more frequent among men [8] whereas in a Polish study they were more frequent among women [10].…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported the factors associated with unmet needs and inequalities in receiving help among people with dementia or cognitive impairment. In a Chilean study, those with dementia living in the community were less likely to receive help if they were men and if they had a lower level of education (1). In the community in the United States, higher unmet needs among those with dementia were associated with non-white ethnicity, lower income, less impairment in activities of daily living, and more symptoms of depression (5).…”
Section: Introductionmentioning
confidence: 99%
“…People with impaired cognitive function (ranging from poor performance in memory and orientation tasks to the neurodegenerative disorder dementia) often have greater needs for assistance in daily activities compared to older people without cognitive di culties (1)(2)(3). Unmet needs are frequently observed among people with dementia, with over 90% having at least one unmet need (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%